2016
DOI: 10.1007/s00059-016-4446-0
|View full text |Cite
|
Sign up to set email alerts
|

Timing and long-term prognosis of recurrent MI after primary angioplasty

Abstract: Although ST was associated with a significant increase in adverse events in the early recovery period, in the long term, MACCE and all-cause mortality rates were comparable to those for NSRMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
3
3
0
Order By: Relevance
“…Likewise, Kukreja et al also reported higher mortality rates in patients with ACS secondary to EST, whereas VLST and LST had no apparent increase in mortality. Equivalent long‐term outcomes of STEMI‐related VLST compared to de novo lesions causing STEMI were also reported by Viveiros Monteiro et al The lack of independent association between LST and VLST and worse outcomes on multivariate analysis in our study corroborate these findings. A possible explanation for the poorer outcomes with EST compared to LST and VLST is the vulnerability of the myocardium in the early recovery period following PCI to acute insults such as EST, particularly that the majority of ST occur in patients with previous ACS or history of MI .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Likewise, Kukreja et al also reported higher mortality rates in patients with ACS secondary to EST, whereas VLST and LST had no apparent increase in mortality. Equivalent long‐term outcomes of STEMI‐related VLST compared to de novo lesions causing STEMI were also reported by Viveiros Monteiro et al The lack of independent association between LST and VLST and worse outcomes on multivariate analysis in our study corroborate these findings. A possible explanation for the poorer outcomes with EST compared to LST and VLST is the vulnerability of the myocardium in the early recovery period following PCI to acute insults such as EST, particularly that the majority of ST occur in patients with previous ACS or history of MI .…”
Section: Discussionsupporting
confidence: 90%
“…The outcomes of ACS secondary to ST compared to de novo lesions have been previously described in literature . Several factors could explain the absence of significant difference of mortality between the two groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The finding of the current study that the risk of mortality increases with more AMIs within shorter TI is in line with previous studies showing worse short-term mortality in cases of ReAMI [5,15,18,25]. This could be explained by the higher rate of stent thrombosis, which is associated with dismal outcomes, particularly during the relatively early period [6,15].…”
Section: Discussionsupporting
confidence: 91%
“…The rate of patients with ReAMI in the current study (≥2 admissions with an AMI) was 18.9%: higher compared with some previous studies [5,6,11,13,14], nearly identical to a study by Viveiros et al [15] and lower from that reported by Motivala et al [9]. These differences stem mostly from the length of the follow-up period and the methodology used in the current study, which focused on analyzing patients according to the exact number of AMIs and not only on separating first events from ReAMIs.…”
Section: Discussionsupporting
confidence: 85%